TRADISI PULANG BAINDUOK SEBAGAI SUATU SISTEM INTEGRASI KELUARGA DIKENAGARIAN PULAU GADANG KECAMATAN XIII KOTO KAMPAR KABUPATEN KAMPAR - Renol Panjaitan; Jonyanis " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
A cultural history of the area first studied population itself. KenagarianPulau Gadang is included in Kampar administration area adjacent to SumatraBarat culture is synonymous with, which consists of the Desa Pulau gadang andthe village of Koto Masjid as a region located Kenagarian the Kecamatan XIIIKoto Kampar. Kenagarian Pulau Gadang Inscribed Stone districts connected byroad. Road conditions are mostly in good condition. In general, peopleKenagarian Pulau Gadang has a fairly high mobility. Mobility is evidenced by themany people both in and out of and into the Koto Masjid every day. Populationmobility is strongly supported by aksibilitas area fairly easily both to the districtand the city center. Humans need other humans to live together and cooperate. Hewas determined to live in groups and society. Small groups in society PulauGadang is a tribal village, while the largest group, are seen from the perspective ofindigenous villages. Tribe as the smallest group, must be well understood andinternalized by society Pulau Gadang. Bainduak home is open to anyone whocomes to the village of Pulau Gadang of any tribe as Batak, Jawa, Minang,Malayu, Nias, Bugis and others, for non-Muslims who return bainduak theyshould convert to Islam. Because in the Desa Pulau Gadang Muslim communityall. People who wander are required to place another person can to theenvironment in which it is located. Entrants must be able to take care of theenvironment around them, become part of his new community. Someone must befused with the migrating into their new hometown. Bainduak home not only forimmigrants, there is also a return bainduak because someone found a soul mate inthe Island Tower. Before the wedding ceremony the bride and groom should lookfor the tribe in the village of Pulau Gadang.Keyword; Tradition, Bainduak, Home As, A Family Systems Integration